THE IMPORTANCE OF INDIVIDUAL FREEDOM AND THE ROLE OF SOCIETY IN LIMITATION OF PERSONAL FREEDOM - Sarsenbayeva Mariya Agatovna (Innovate Conferences, 2026)
In particular, this article covers the following: tension between individual freedom and societal control; maintaining both personal liberty and social order; Public Safety and Order, Protection of Rights, and Proportionality; free speech and hate speech laws.
Keywords: Social philosophy, Individuals, freedom, Cybersecurity specialists, public safety, social order.